Civil Identity of Youth in the Conditions of Regional Social and Political Tension - Siruikova, Iana Alexeevna; Khramova, Evgeniya Valer’evna (Cuestiones Políticas, 2020)
The article discusses the process of building the civil identity of young people in conditions of social and political tension, from a regional perspective. The formation of civic identity is a real problem of modern Russian society. The process is complicated by changes in the socio-political of the various regions. The media stimulates public discourse around the protest activity of young people. In the context of this scientific interest, the research presented in this article is carried out. Its empirical material is obtained during a grant study by the authors at the end of 2019. The research methodology is based on conflict resolution technology. As an empirical basis, materials from three focus group surveys, fifteen in-depth interviews and regional-minded internet resource content analysis on the topics of socio-political youth activity were interpreted. It is concluded that the republic of Tartaristan, as one of the regions of the Russian federation that has specifics in its economic, ethnic, and religious life, has become a platform for gathering empirical information.